1990
DOI: 10.2527/1990.68103244x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol extraction and heat treatment of soybean flakes on function and morphology of pig intestine.

Abstract: Digesta and tissue samples were collected from the intestinal tracts of 27 pigs to determine the relationship between intestinal morphology and the utilization of nutrients from soybean flakes. Soybean flake treatments were under-, intermediate-and overprocessed (Le., 5, 20 and 60 min of autoclaving) either without extraction or with heating before or after extraction with a 55% ethanol-water mixture. Final BW was greatest (P < .001) for pigs fed soybean flakes given 20 min of heat treatment. There was a trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
1
16
0
3
Order By: Relevance
“…When animals have a higher cell renewal of the intestinal mucosa they have a greater crypt depth due to hyperplasia, as a result of the high mitotic activity (HANCOCK et al, 1990). Thus, the results obtained for crypt depth suggest there was an increased cell renewal stimulated by the diet containing increasing levels of sunflower cake, independent of the use of the EC.…”
Section: Resultssupporting
confidence: 48%
“…When animals have a higher cell renewal of the intestinal mucosa they have a greater crypt depth due to hyperplasia, as a result of the high mitotic activity (HANCOCK et al, 1990). Thus, the results obtained for crypt depth suggest there was an increased cell renewal stimulated by the diet containing increasing levels of sunflower cake, independent of the use of the EC.…”
Section: Resultssupporting
confidence: 48%
“…Hancock (1990) and Li et al (1991) concluded that there is a positive correlation between VH in the small intestine and the growth rate of piglets.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hancock (1990), CD is an indicator of the degree of epithelial cell hyperplasia, which is related to antigenicity of the diet, among other factors. A lower CD indicates less aggression of the diet to the morphology of the intestinal wall (Li et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Hancock et al (1990) observed the highest villus height in piglets after feeding ethanol-extracted and heat-treated soybean meal. They concluded that a better piglet growth rate was associated with higher villus height.…”
mentioning
confidence: 99%